2013
DOI: 10.1016/j.urology.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Dapoxetine Treatment in Patients With Lifelong Premature Ejaculation: The Reasons of a “Waterloo”

Abstract: OBJECTIVETo assess both the acceptance and the discontinuation rates from dapoxetine, the first oral pharmacological agent indicated for the treatment of premature ejaculation (PE). METHODSOne hundred twenty consecutive potent patients (mean age 40.3 years; range 18-63 years) seeking medical treatment for lifelong PE were enrolled in a prospective phase II study. Moreover, they were assessed regarding detailed medical and sexual history, intravaginal ejaculatory latency time (IELT), International Index of Erec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 19 publications
5
69
0
Order By: Relevance
“…We didn't see anyone suffer from dry mouth which may be associated with take much water when have drugs. The incidence of adverse events of dapoxetine is relate to the dose,on-demand use of dapoxetine 30mg and 60mg for patients with LPE can be tolerated.Mondaini N et al showed 20% of patients with LPE seek for treatment refused pharmacotherapy by dapoxetine,and nearly 90% of patients started therapy discontinued after 1 year [22].…”
Section: Resultsmentioning
confidence: 99%
“…We didn't see anyone suffer from dry mouth which may be associated with take much water when have drugs. The incidence of adverse events of dapoxetine is relate to the dose,on-demand use of dapoxetine 30mg and 60mg for patients with LPE can be tolerated.Mondaini N et al showed 20% of patients with LPE seek for treatment refused pharmacotherapy by dapoxetine,and nearly 90% of patients started therapy discontinued after 1 year [22].…”
Section: Resultsmentioning
confidence: 99%
“…3 Dapoxetine is the first oral pharmacologic agent developed to treat PE and is the only SSRI approved for such treatment in more than 60 countries. 4 The introduction of dapoxetine was associated with high expectations, given the optimal efficacy-safety profiles evident in phase 3 trials. 5 However, although several clinical studies have confirmed drug efficacy in increasing the intravaginal ejaculation latency time (IELT) and safety, the rate of discontinuation is as high as when taking off-label SSRIs.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, although several clinical studies have confirmed drug efficacy in increasing the intravaginal ejaculation latency time (IELT) and safety, the rate of discontinuation is as high as when taking off-label SSRIs. 4,5 The discontinuation rate is high compared with those of PDE5 inhibitors in patients with erectile dysfunction (ED). 4,6 To date, dapoxetine is the only approved medical treatment for PE; no second-line therapy is available in those who do not respond or who refuse to take dapoxetine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations